Length–weight and length–length relationships for two gobiids from the Anzali Wetland, in the southern Caspian Sea basin. (6th April 2018) - Heidari, A.; Mousavi‐Sabet, H.; Sattari, M.; Alavi‐Yeganeh, M. S.; Abbasi, K.
Summary: Length–weight (LWR) and length–length (LLR) relationships were estimated for specimens of two gobiid species collected from the Anzali Wetland and its related streams in the southern Caspian Sea basin, in August 2017. These represent the first reports of LWR and LLR data for Rhinogobius cf. similis Gill, 1859 (37°28′13″N, 49°20′33″E; 50 individuals) and Proterorhinus nasalis (De Filippi, 1863) (36°54′10.89″N, 53°48′48.33″E; 30 individuals) from the Wetland. A new maximum length is reported for P. nasalis . The length–weight parameter b for these species ranged a minimum of 2.99 for Rhinogobius cf. similis to a maximum of 3.04 for P. nasalis with regression coefficients ( r 2 ) ranging from .95 to .97. All LLRs were highly significant ( r 2 >.96).